Bridging the gap – the direct and indirect benefits of digital adoption among smallholders / Noor Azuan Hashim and Nurdayana Hidayah Jan Mohd Suzaini - Hashim, Noor Azuan; Mohd Suzaini, Nurdayana Hidayah Jan (2023)
This study attempts to investigate the actual and current situation of digital technologies adoption for information dissemination on palm oil among smallholders and opinion leaders in Malaysia. This study has carried-out both quantitative and qualitative methods to explore the issues of being studied. 579 responses were received from survey using Google form link. In addition, 12 respondents were randomly chosen from the list of 579 and that had agreed to be interviewed through phone calls. This study documents that oil palm smallholders have a high level of belief that the use of digital technology particularly smart phones can assist them on information about palm oil as well as to help them to achieve performance of their oil palm farming business. The study uses single respondent and cross-sectional data that might have some limitations in terms of data rigorousness and findings generalizability. In addition, the survey is conducted via online – Google form and interviews via telephone. It is much better if it can be conducted face-to-face. The findings provide important managerial and policymaking implications. There is very scarce research focusing on the readiness, adoption, and the effectiveness of digital technologies on information dissemination about oil palm, particularly among palm oil smallholders and this paper intends to discuss and to enrich understanding on this issue. This group is often marginalized because they are still considered irrelevant, and thus the finding of this study will contribute to these smallholders, or in general the farmers. In addition, using mixed method is hardly used elsewhere and this study had made this happen.